Digital scalar pulse-width modulation a simple approach to introduce nonsinusoidal modulating waveforms. - Jacobina, C.B (IEEE Transactions on power electronics)
The digital scalar pulse-width modulation (DSPWM) gathers the characteristics of simplicity of implementation found in the regular sampling with the flexibility of manipulation of the switching patterns in the space vector modulation (SVPWM). This paper establishes a correlation between the SVPWM and DSPWM techniques. It also shows how to make the DSPWM strategy equivalent to the SVPWM technique without losing its simplicity of implementation. By using such an equivalence concept a microprocessor-based scheme, which uses standard timer circuits and a simple software algorithm, is proposed to implement the DSPWM technique. The introduction of the ?distribution ratio? in this technique, allows the development of a systematic approach for implementing either conventional or any modified vector strategies without changing the modulator scheme. This corresponds to generating any attractive nonsinusoidal modulating signals (NSMS) in the carrier-based modulation techniques. Furthermore, the simple digital blocks can be easily implemented as a specialized integrated circuit. Simulated and experimental results demonstrate the validity of the proposed methods